2015
DOI: 10.1021/acs.energyfuels.5b01377
|View full text |Cite
|
Sign up to set email alerts
|

Chemical-Looping with Oxygen Uncoupling of Different Coals Using Copper Ore as an Oxygen Carrier

Abstract: Chemical-looping with oxygen uncoupling (CLOU) has been considered as a revolutionary technology for lowenergy consumption CO 2 capture. In this work, the performance of copper ore in the CLOU processes for diverse ranks of coal was examined in a batch-scale fluidized-bed at various temperatures. Typical Chinese coals (GaoPing anthracite, FuGu bituminous coal, and ShengLi lignite) were used as fuel. The effects of temperature and coal rank on the redox behavior, carbon conversion rate, and instantaneous rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…Furthermore, the PWm–20% sample after 10 redox cycles of testing showed a slightly higher BET surface area than the UOC sample after 10 redox cycles of testing, thereby showing better reactivity. 43 Thus, the BET surface areas indicated that RAm–20%, ULm–20%, and PWm–20% had better cycle stability, which was consistent with previous research conclusions. 44 …”
Section: Results and Discussionsupporting
confidence: 91%
“…Furthermore, the PWm–20% sample after 10 redox cycles of testing showed a slightly higher BET surface area than the UOC sample after 10 redox cycles of testing, thereby showing better reactivity. 43 Thus, the BET surface areas indicated that RAm–20%, ULm–20%, and PWm–20% had better cycle stability, which was consistent with previous research conclusions. 44 …”
Section: Results and Discussionsupporting
confidence: 91%
“…All of the parameters present an upward trend with the increase of the temperature. As seen from Table , the temperature is a vital factor affecting the average carbon conversion rate, which was also proven by our previous work . The decrement of combustion efficiency is mainly ascribed to more carbon residues at a relatively low temperature.…”
Section: Resultssupporting
confidence: 75%
“…The carbon conversion rate x C and instantaneous carbon conversion rate x inst (on the basis of remaining unreacted carbon) are calculated as The instantaneous oxygen transfer rate during the reduction process, x O 2 ,red ( t ), is determined on the basis of the mass balance of the O atoms in the reactor where F i (including O 2 , CO 2 , CO, H 2 , or CH 4 ) is the molar gas flow in the exhaust gas during the reduction process, which can be calculated as To measure oxygen leaving with H 2 O generating from hydrogen oxidation in the coal, it is assumed that the hydrogen evolution is proportional to the carbon evolution; i.e., the ratio C/H maintains the same value in the gas components as in the coal. Considering the fact that a little methane and hydrogen are detected in the experiment, the H 2 O flow rate is calculated as where f H/C is the hydrogen/carbon molar ratio in the coal.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Choosing the right oxygen carrier and better operating conditions are some of the key issues in the chemical-looping gasification process. [2][3][4][5][6] Guo et al suggested that multifunctional oxygen carrier compounds, such as Ca-based oxygen carriers with K or Na pendant groups, coupled with catalytic gasification, could effectively accelerate coal gasification, but the systems suffered alkali metal loss during the recycling process. [7,8] Moreover, Cu-based oxygen carriers usually exhibit greater oxygen donating capacity and much higher reactivity, which can effectively accelerate char gasification.…”
Section: Introductionmentioning
confidence: 99%